2020
DOI: 10.1158/1535-7163.mct-19-0709
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of the EPR Effect in Tumor Xenografts Using Small 15 nm Diameter Polyethylene Glycols Labeled with Zirconium-89

Abstract: The goal was to develop and characterize a companion diagnostic for the releasable PEG 40kDa $SN-38 oncology drug, PLX038, that would identify tumors susceptible to high accumulation of PLX038. PEG conjugates of the zirconium ligand desferroxamine B (DFB) of similar size and charge to PLX038 were prepared that contained one or four DFB, as well as one that contained three SN-38 moieties and one DFB. Uptake and associated kinetic parameters of the 89 Zr-labeled nanocarriers were determined in tumor and normal t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…PBPK modelling has been a useful tool for evaluating the in vivo distribution of NPs. However, to date, there are few papers that have referred to polymeric NPs in PBPK modelling [7,8,[11][12][13][14]21,22], and so far, there have been no reports dealing with mPEG-PCL NPs using PBPK models. We synthesised five mPEG-PCL NP formulations involving different sizes, different ratios of mPEG-PCL/PCL, and different weights of coating mPEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBPK modelling has been a useful tool for evaluating the in vivo distribution of NPs. However, to date, there are few papers that have referred to polymeric NPs in PBPK modelling [7,8,[11][12][13][14]21,22], and so far, there have been no reports dealing with mPEG-PCL NPs using PBPK models. We synthesised five mPEG-PCL NP formulations involving different sizes, different ratios of mPEG-PCL/PCL, and different weights of coating mPEG.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with PBPK models of inorganic metallic NPs and QD/NPs, much less research involving organic polymeric NPs and cellular phagocytosis has been reported. To date, there have been only a small number of reports concerning polymeric NPs and mechanisms involved in cellular phagocytosis [7,[11][12][13][14][15]. For example, Li et al evaluated the biodistribution of polyethylene glycol-coated polyacrylamide (PEG/PAA) NPs using a PBPK model based on the mechanism of cellular phagocytosis, which indicated that the phagocytosing cell (PC) system greatly affected the pharmacokinetic behaviour of PEG/PAA NPs [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the tumor Cmax is ≈72 h for star copolymers with %ID/g tumor at ≈15%, [ 109 ] in excess of 48 h for PEG‐b‐pHPMA‐based polymeric micelles with 18.6% ID/g, [ 99 ] and 14% of injected dose by 4 days for 15 nm 4‐arm branched PEG. [ 110 ] The greater accumulation and delayed Cmax is thought to be due to the longer circulation time and potentially larger number of particles giving more time to penetrate the tumor. Beckford Vera et al.…”
Section: Applying Learnings From Small Molecule Drug Developmentmentioning
confidence: 99%
“…have published a pre‐clinical study using using 89 Zr labeled PEG conjugates of similar size and charge to their SN38 clinical candidate, PLX038 suggesting that these labeled conjugates could be used as effective diagnostic to identify tumors susceptible to PLX038 and other similar size nanocarriers. [ 110 ] A 89 Zr labeled PET with the polymeric micelle CPC 634 study revealed enhanced and prolonged tumor accumulation in humans with uptake in 43% of evaluable tumor lesions (16/37). Again this radiolabeled CPC‐6634 offers the opportunity to aid patient selection.…”
Section: Applying Learnings From Small Molecule Drug Developmentmentioning
confidence: 99%
“…Passive targeting also involves the use of other innate characteristics of nanoparticles that can affect tumour targeting. The ability of nanoDDSs to passively target tumours has been shown many times in in vivo animal models through the use of different imaging techniques [22,23]. Unfortunately, passive targeting based on the EPR effect has shown heterogenous and questionable efficacy in tumour targeting.…”
Section: Introductionmentioning
confidence: 99%